Frontiers in the Interaction of Chemically Reactive Species From Gaseous Plasma With Hydrophobic Polymers - Zaplotnik, Rok; Mozetič, Miran (Frontiers in Physics, 2022)
Surface functionalization of polymers by chemically reactive oxygen is a standard technique for increasing the surface energy of polymers. The technique, however, usually does not provide the desired surface finish of many polymers, including highly hydrophobic polymers like those rich in fluorine. The disappointing results are due to an incomplete understanding of the interaction between the plasma species and polymers on the atomic scale. The current state is presented, and recent advances in both theoretical and experimental descriptions of the surface mechanisms are illustrated. The scientific community faces challenges in both plasma characterization, separation of specific reactants, and detailed study of the interaction on the atomic scale. The effects of vacuum-ultraviolet radiation and its synergy with neutral reactive plasma particles are often neglected, but recent articles represent a pathway to the appropriate design of the experimental systems, which will enable systematic measurements of the evolution of surface functional groups versus the fluence of selected plasma species.